Analysis of Business Combination Implementation at PT China Construction Bank Indonesia - Andita Wulandari K; Zanuar Arifin; Amrie Firmansyah (STKIP Singkawang, 2018)
This study aims to review the implementation of mergers conducted by the company. In Indonesia, merger activities are regulated in Indonesia Statement of Financial Accounting Standards Number 22 (hereinafter referred to as PSAK 22) concerning Business Combinations. Increased merger activities in the business world are driven by changes in economic conditions. The rise of merger and acquisition activities was caused by various things, such as technological advances, increasing financial conditions, excess capacity/financial failure, international market consolidation and deregulation.The research method used in this research is qualitative descriptive with case studies of business combination events that occurred between PT Bank Windu Kentjana Internasional, Tbk as the party which received the merger and PT Bank Antardaerah as the company which joined. Regarding ownership, the name of PT Bank Windu Kentjana Internasional, Tbk changed to PT China Construction Bank Indonesia, Tbk (PT CCB Indonesia, Tbk).The results of this study indicate that in general, the consolidated report of PT CCB Indonesia, Tbk for the period ended December 31, 2016, in general, has been prepared by PSAK 22, 2015.